Quantitative Estimate of CO2 Emission Reduction from Reuse of Automobile Parts in Japan - Masato Inoue; Sota Takahashi; Mitsunobu Fujita; Takao Mori; Motohiro Tamaki; Shigeyuki Suzuki; Akihiro Hayakawa (International Journal of Supply Chain Management, 2017)
In general, reusing automobile parts reduces not only the cost of replacing the failed parts but also the environmental load of manufacturing new parts. However, these effects have not yet been quantified. The present study focuses on determining the emitted CO2 during production and quantitatively evaluating its reduction by the reuse of automobile parts. First, CO2 emissions are calculated during the reused parts production process at the factory site. Thirty-nine automobiles from 27 models prepared in Japan are examined to measure the amount of CO2 emitted in the production of new parts. Furthermore, the CO2 emission reduction effect for different automobile models is estimated through multiple regression analysis. The CO2 emissions are assumed to be the objective variable, whereas the explanatory variables are derived from the data provided in the automobile inspection certificates. The presented quantitative estimate of CO2 emission reduction owing to the exploitation of reused parts is expected to promote policies for further reducing CO2 emissions and arouse public awareness regarding the benefits of recycling automobile parts.